2022
DOI: 10.1210/clinem/dgac261
|View full text |Cite
|
Sign up to set email alerts
|

Increased Adipose Tissue Indices of Androgen Catabolism and Aromatization in Women With Metabolic Dysfunction

Abstract: Background Body fat distribution is a risk factor for obesity-associated comorbidities, and adipose tissue dysfunction plays a role in this association. In humans, there is a sex difference in body fat distribution, and steroid hormones are known to regulate several cellular processes within adipose tissue. Our aim was to investigate if intra-adipose steroid concentration and expression or activity of steroidogenic enzymes were associated with features of adipose tissue dysfunction in individ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 79 publications
0
9
0
Order By: Relevance
“…These pathways are related to metabolism, genetic information processing, and environmental information processing. The alteration of steroid biosynthesis regulates lipid metabolism, and the change in local steroid concentration can cause abnormal adipose tissue function, such as dyslipogenesis or abnormal production of adipokines, eventually leading to lipid metabolism disorder ( Ostinelli et al, 2022 ; Wawrzkiewicz-Jałowiecka, Lalik & Soveral, 2021 ). Twenty candidate genes of interest were enriched in steroid biosynthesis, and the leading edge included 14 genes ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These pathways are related to metabolism, genetic information processing, and environmental information processing. The alteration of steroid biosynthesis regulates lipid metabolism, and the change in local steroid concentration can cause abnormal adipose tissue function, such as dyslipogenesis or abnormal production of adipokines, eventually leading to lipid metabolism disorder ( Ostinelli et al, 2022 ; Wawrzkiewicz-Jałowiecka, Lalik & Soveral, 2021 ). Twenty candidate genes of interest were enriched in steroid biosynthesis, and the leading edge included 14 genes ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Estrogens are synthesized from androgens using cytochrome P450 aromatase, which is encoded by the CYP19 gene 66 . After menopause, estrogen biosynthesis is primarily mediated by peripheral aromatization of androgen precursors in adipose tissue 67 …”
Section: Molecular Mechanisms Of Csc Regulation By Adipocytesmentioning
confidence: 99%
“…66 After menopause, estrogen biosynthesis is primarily mediated by peripheral aromatization of androgen precursors in adipose tissue. 67 Although exposure to estradiol promotes the growth and maintenance of papillary thyroid CSCs 68 and the importance of estrogen in breast cancer is well established, the effects of estrogen on breast CSCs are not fully understood. Several studies have reported that estrogens alone do not increase, and breast CSCs lack expression of estrogen receptor (ER) or express it at very low levels.…”
Section: Biosynthesis Of Estrogenmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are in line with those of a previous study reporting that insulin significantly stimulates A4 and T production in SAT ( 58 ). Conversely, in the VAT of women with obesity, increased aromatase activity, representing the hypertrophy of adipocyte, parallels the increased androgen catabolism via enhancing AKR1C2 function ( 59 ). In addition, the expression level of AR in the VAT may be higher than that in the SAT of women with PCOS, making the VAT more vulnerable to androgen exposure ( 35 ).…”
Section: Androgen Synthesismentioning
confidence: 99%